Innovative Learning in Character Building for Elementary School Students - Fitriana, Atika (Universitas Sebelas Maret, 2022)
The learning process that is applied is not effective enough to be able to shape student character, one way to integrate character education is by using innovative learning. Teachers should innovate in learning because many teachers have not been able to integrate character education in learning. The purpose of this article is to describe innovative learning as one way of shaping student character in elementary schools. The research method used is a literature study research method sourced from books, journals and relevant research results. The data analysis technique used is content analysis. The results of this study indicate that the character building of elementary school students can be done by applying innovative learning in all subjects, because learning is integrated with various characters. One example of an innovative learning model that can shape student character is the Contextual Teaching and Learning (CTL) learning model. Through innovative learning models, students are expected to have characters that can be applied in everyday life.